PENGARUH MEDIA PEMBELAJARANTERHADAP HASIL BELAJAR SEJARAH PADASISWA KELAS X DI SMA NEGERI 8 PADANGSIDIMPUANTAHUN AJARAN 2021-2022 - Ali Padang (Pendidikan Sejarah, 2022)
History of science or field of study of history. Among them are many who question the usefulness of things related to history or, more precisely study the history both for individuals and for society. So the sense of history is a story of the past who have been vetted and have relevance to the present. To improve learning outcomes History students, the school and the teachers at SMAN 8 Padangsidimpuan already made several attempts including by improving the way teachers teach, give motivation to students, equipping school facilities and infrastructure, and others. One effort that can be used to improve student learning outcomes History is with the implementation of the media. Interested in the problems described above, the authors tried to examine the extent to which,